Peculiarities of conducting undercover investigative (search) actions in the investigation of robberies and robberies committed under martial law - Oliynychuk, Roman; Kanyuka, Valerii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The characteristic features of secret investigative (research) actions in the investigation of robberies and robberies attacks committed during martial law are considered. The views of scientists on the categories related to the specifics of the use and conduct of covert investigative (research) actions in the investigation of robberies and robberies attacks committed during martial law were analyzed. The importance of proper planning and conducting covert investigative (research) actions of law enforcement officers for the successful disclosure of robberies and robberies attacks committed during martial law is substantiated. The specifics of conducting separate secret investigative (research) actions in the investigation of robberies and robberies attacks committed under martial law were identified, and corresponding author's conclusions were drawn. The Institute of Covert Investigative (Investigative) Actions is provided for in the Criminal Procedure Code of Ukraine as an effective toolkit for performing such tasks of criminal proceedings as protecting individuals, society and the state from criminal offenses, as well as ensuring a quick and complete investigation and trial so that everyone, whoever committed a criminal offense was prosecuted to the extent of their guilt, no innocent person was charged or convicted, no person was subjected to unjustified procedural coercion, and that due process of law was applied to every participant in criminal proceedings. There are many different ways of committing robberies and robberies, so criminals choose one or another method in each specific case depending on specific circumstances. Based on this, law enforcement officers also need to choose the type of secret investigative (search) action and the immediate time and method of its implementation, depending on the specific circumstances of the case.